Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar : Penelitian - Naia Zetira Rodri; Muslihin; Aisyah Arrahman; Wahyudi; Hariki Fitrah; Rahmi Novalita; Mauliana Wayudi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to improve student learning outcomes on the basic competency of geographical conditions and ocean exploration through the guided inquiry learning model in Grade VIII of SMP Negeri 1 Peusangan. Using a two-cycle Classroom Action Research (CAR) method, each cycle involved planning, implementation, observation, and reflection. Data were collected through learning outcome tests, observations of teacher and student activities, and documentation. Results showed an increase in learning mastery from 70% in Cycle I to 90% in Cycle II. Teacher activity rose from 81.11% to 91.11%, while student activity increased from 75.56% to 86.67%. The guided inquiry model effectively enhanced learning outcomes, encouraged critical thinking, and increased student engagement and interest in the learning process.